Induction of unique macrophage subset by simultaneous stimulation with LPS and IL-4 - Ishida, Kei; Nagatake, Takahiro; Saika, Azusa; Kawai, Soichiro; Node, Eri; Hosomi, Koji; Kunisawa, Jun (Frontiers in Immunology, 2023)
Macrophages manifest as various subtypes that play diverse and important roles in immunosurveillance and the maintenance of immunological homeostasis in various tissues. Many in vitro studies divide macrophages into two broad groups: M1 macrophages induced by lipopolysaccharide (LPS), and M2 macrophages induced by interleukin 4 (IL-4). However, considering the complex and diverse microenvironment in vivo, the concept of M1 and M2 is not enough to explain diversity of macrophages. In this study, we analyzed the functions of macrophages induced by simultaneous stimulation with LPS and IL-4 (termed LPS/IL-4-induced macrophages). LPS/IL-4-induced macrophages were a homogeneous population showing a mixture of the characteristics of M1 and M2 macrophages. In LPS/IL-4-induced macrophages, expression of cell-surface M1 markers (I-Ab) was higher than in M1 macrophages, but lower expression of iNOS, and expression of M1-associated genes (Tnfα and Il12p40) were decreased in comparison to expression in M1 macrophages. Conversely, expression of the cell-surface M2 marker CD206 was lower on LPS/IL-4-induced macrophages than on M2 macrophages and expression of M2-associated genes (Arg1, Chi3l3, and Fizz1) varied, with Arg1 being greater than, Fizz1 being lower than, and Chi3l3 being comparable to that in M2 macrophages. Glycolysis-dependent phagocytic activity of LPS/IL-4-induced macrophages was strongly enhanced as was that of M1 macrophages; however, the energy metabolism of LPS/IL-4-induced macrophages, such as activation state of glycolytic and oxidative phosphorylation, was quite different from that of M1 or M2 macrophages. These results indicate that the macrophages induced by LPS and IL-4 had unique properties.